PARTISIPASI MASYARAKAT DALAM PENGELOLAAN DESA WISATA SETANGGOR KABUPATEN LOMBOK TENGAH - lalu Triawan Mundra; Fathurrahim Fathurrahim; Sri Wahyuningsih (Program Studi S1 Pariwisata, Sekolah Tinggi Pariwisata Mataram, 2023)
This study discusses about community participation in the management of the Setanggor tourism village, Central Lombok Regency. The data collection in this study used the method of observation, interviews and documentation with a qualitative descriptive approach. The results showed that the form of community participation in the management of tourism villages which was entirely based on community empowerment or community based tourism (CBT) and was applied in the form of direct participation or the community had directly carrying out tourism activities in Setanggor Village by taking the role of subject and object simultaneously, meaning that in implementing tourism activities in Setanggor Village, the community becomes tourism actors and managers, and at the same time becomes an object that can be enjoyed by tourists through performing arts and crafts attractions.